2020
DOI: 10.1088/1757-899x/999/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Waste Reduction with Lean Manufacturing Model in an Alpaca Wool Workshop

Abstract: This paper proposes the design of a quasi-experimental time-series model comprising lean manufacturing tools—such as the value stream mapping and 5S’s—with the aim of reducing the level of waste and losses in a micro-company dedicated to the production of Alpaca wool clothing in Junín, Perú. The model implementation managed to reduce the level of waste by 7%, increase the efficiency in material consumption, and reduce the cycle time and total supply time. The implementation of the model allowed reducing the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…As can be seen in the results obtained, the indicator with the greatest variation was the total time of mold change with a variation of 52.96% with respect to the initial scenario, and exceeding by 18.49% those proposed by the authors Ames et al [17] and in 10.96% from those obtained in Dogan et al [16], it should be noted that through the SMED tool it was possible to convert as many activities as possible into external, managing to go from 51.47 to 24.21 minutes. Likewise, the 5S audit indicator presented a variation of 44% thanks to the classification of elements, release of areas, creation of cleaning policies and implementation of organizers; however, results showed a value 4% below what was proposed by the authors Cristobal et al [9], who managed to reach 80% in the final audit of 5s. In addition, with regard to the indicators of SLP, transfer time, it was possible to reduce from 31.17 to 17.8 hours, decreasing by 42.89%, surpassing Suhardi, Juwita and Astuti.…”
Section: Validation Design Improvementmentioning
confidence: 66%
See 1 more Smart Citation
“…As can be seen in the results obtained, the indicator with the greatest variation was the total time of mold change with a variation of 52.96% with respect to the initial scenario, and exceeding by 18.49% those proposed by the authors Ames et al [17] and in 10.96% from those obtained in Dogan et al [16], it should be noted that through the SMED tool it was possible to convert as many activities as possible into external, managing to go from 51.47 to 24.21 minutes. Likewise, the 5S audit indicator presented a variation of 44% thanks to the classification of elements, release of areas, creation of cleaning policies and implementation of organizers; however, results showed a value 4% below what was proposed by the authors Cristobal et al [9], who managed to reach 80% in the final audit of 5s. In addition, with regard to the indicators of SLP, transfer time, it was possible to reduce from 31.17 to 17.8 hours, decreasing by 42.89%, surpassing Suhardi, Juwita and Astuti.…”
Section: Validation Design Improvementmentioning
confidence: 66%
“…Lean tools in the manufacturing industry aim to reduce waste and increase the level of customer satisfaction [9] [10]. Studies agree that to reduce waste and optimize production processes, tools such as 5S and SMED are among the most effective [11].…”
Section: B Lean Manufacturing (5s and Smed)mentioning
confidence: 99%
“…Shahriar et al (2022) also demonstrated its effectiveness at reducing motion and waiting time waste, by achieving up to 20.40% operation time reduction in a plastic bag manufacturing company through its implementation. Cristobal et al (2020) implemented the 5S methodology in an alpaca wool workshop to obtain a 7% waste reduction, further proving its versatility and usefulness.…”
Section: Application Of 5smentioning
confidence: 94%
“…In many cases, organizations aim to reshape personnel recruitment practices, leadership and motivation to develop a better culture [16]. For example, in a Peruvian textile company, an organizational culture based on order, cleanliness and discipline was implemented, reducing waste by 7% and reducing the cycle time and total supply time [17]. The exchange of knowledge has been facilitated by information technology, but organizations have not yet scaled up such exchange, although implementing it would improve organizational performance, reduce costs, promote innovation and reduce repetitive work [18].…”
Section: Introductionmentioning
confidence: 99%